Effects of Sedentariness and Repetitive Joint Activities on the Health of E-sports Athletes - Bi, Mingyuan (International Journal of Social Sciences and Public Administration, 2024)
As an emerging sport, eSports has received more and more attention, especially the impact of eSports on health is a topic of interest to researchers. Combined with key statistics, Gaming requires competitive rivalry through electronic systems, and athletes need to sit and stand for long periods of time and engage in repetitive joint activities, which also leads to physical injuries and to a certain extent affects their technical and tactical performance as well as their normal lives. This paper first analyzes the characteristics of eSports and the essence of the impact on eSports athletes’ health and dissects the health problems it brings and the mechanisms that generate them. Finally, corresponding countermeasures and suggestions are proposed, which are expected to raise the awareness of injury prevention among athletes engaged in e-sports as well as enthusiasts in general, and thus reasonably improve the level of e-sports in China.